Upright emplacement of the Gibraltar slab and the origin of rifting in adjacent foreland and Backarc Basins - Pengfei Ma; Shaofeng Liu; Guillermo Booth-Rea; Huiping Zhang; Ting Yang (Communications Earth & Environment)
Abstract Back-arc basins in subduction systems usually form following discrete subduction-related extension stages. However, in the westernmost Mediterranean, the initiation of Cenozoic extension associated with the Valencia Trough and Algerian Sea Basin introduced two extension centers nearly simultaneously in the Gibraltar subduction system, and this presents a challenge to understanding their underlying dynamics. We built three-dimensional time-dependent geodynamic models constrained by tectonic reconstructions to determine the role that the Gibraltar subduction played in shaping unconventional extensional basins. Our results suggest that the Algerian Sea Basin is a typical back-arc basin, whereas the Valencia Trough opened on the subducting plate during the rotational rollback of the Gibraltar slab. Moreover, the Valencia Trough extension likely delayed slab tearing and guided slab sinking before its final detachment, facilitating its ultimate upright positioning. We show how plates and the mantle interact dynamically in a subduction system where the slab asymmetrically rolls back.